„Jakiego skarbu my Polacy nigdyśmy przedtym nie mieli”. Ślady lektury Żywotów świętych Piotra Skargi w katolickich drukach z końca XVI wieku - Sitkowa, Anna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
Four Polish printed matters from the end of 16th century were highlighted in the article. Three of them, The Life and Death of a Princess from Parma (1581); Republic (1594); Joseph the Righteous (1596) refer to Lives of the Saints by Piotr Skarga. This is proof that the book was highly appreciated by the author’s contemporaries as a counter-reformation speculum, outstanding reading for women, and a point of reference for clergymen who wanted to prepare their own speeches. The forth printed matter is another sign of The Lives of Saints popularity (The Benedictine Rule circa 1597). What we find there is a slightly altered version of St. Benedict’s life, which does not mention the name of Piotr Skarga.